2023
DOI: 10.3389/fnagi.2023.1149036
|View full text |Cite
|
Sign up to set email alerts
|

On gaps of clinical diagnosis of dementia subtypes: A study of Alzheimer’s disease and Lewy body disease

Abstract: IntroductionAlzheimer’s disease (AD) and Lewy body disease (LBD) are the two most common neurodegenerative dementias and can occur in combination (AD+LBD). Due to overlapping biomarkers and symptoms, clinical differentiation of these subtypes could be difficult. However, it is unclear how the magnitude of diagnostic uncertainty varies across dementia spectra and demographic variables. We aimed to compare clinical diagnosis and post-mortem autopsy-confirmed pathological results to assess the clinical subtype di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…But with research suggesting that dementia generally and AD dementia specifically are more commonly diagnosed in Black adults, it remains unclear why DLB would be less frequently identified in this population. It is possible that higher rates of copathology in Black adults with dementia [5,6,20] and symptoms associated with that co-pathology (e.g., AD, vascular disease) obscure the clinical picture that might suggest the presence of Lewy body pathology. It is also possible that clinicians are predisposed to give AD dementia diagnoses to Black individuals based on the research showing high prevalence in this population.…”
Section: Dementia and Racementioning
confidence: 99%
See 1 more Smart Citation
“…But with research suggesting that dementia generally and AD dementia specifically are more commonly diagnosed in Black adults, it remains unclear why DLB would be less frequently identified in this population. It is possible that higher rates of copathology in Black adults with dementia [5,6,20] and symptoms associated with that co-pathology (e.g., AD, vascular disease) obscure the clinical picture that might suggest the presence of Lewy body pathology. It is also possible that clinicians are predisposed to give AD dementia diagnoses to Black individuals based on the research showing high prevalence in this population.…”
Section: Dementia and Racementioning
confidence: 99%
“…The prevalence of Lewy body dementia codes was 5.5% in White non-Hispanic adults and 6.1% in Hispanic adults [4]. Multiple studies using the U.S.-based National Alzheimer Coordinating Center (NACC) database identified that fewer Black participants with pathologic Lewy body disease had a clinical suspicion for Lewy body dementia in life compared to White or Hispanic participants [5,6]. Over 96% of participants in clinical trials for Lewy body dementia identify as White [7].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for all-cause dementia include increasing age and female sex, as well as protective factors such as higher education and cognitive or physical activity. Clinical presentation varies greatly with cognitive deficits of memory loss, communication, and language impairments, and in severe cases, aphasia, agnosia, and apraxia [ 4 ]. Dementia is an umbrella term with subtypes of Alzheimer’s dementia (AD), vascular dementia, Lewy body dementia, and frontotemporal dementia.…”
Section: Introductionmentioning
confidence: 99%